Silicone-covered biodegradable magnesium-stent insertion in the esophagus: a comparison with plastic stents. (January 2017) - Zhu, Yue-Qi; Yang, Kai; Edmonds, Laura; Wei, Li-Ming; Zheng, Reila; Cheng, Ruo-Yu; Cui, Wen-Guo; Cheng, Ying-Sheng
Background: We determined the feasibility of, and tissue response to silicone-covered biodegradable magnesium- and plastic-stent insertion into the esophagus in rabbits. Methods: The mechanical compression–recovery characteristics and degradation behaviors of the magnesium stent were investigated in vitro . A total of 45 rabbits were randomly divided into a magnesium- ( n = 15) and a plastic- ( n = 15) stent group, and underwent stent insertion into the lower third of the esophagus under fluoroscopic guidance; a control group ( n = 15) did not undergo the intervention. Esophagography was performed at 1, 2, and 4 weeks. Five rabbits in each group were euthanized at each time point for histological examination. Results: Silicone-covered magnesium stents showed similar radial force to plastic stents ( p > 0.05). The magnesium stents degraded rapidly in an acidic solution, but 90.2% ± 3.1% of the residual mass was maintained after a 2-week degradation in a solution with a pH of 4.0. All stent insertions were well tolerated. Magnesium stents migrated in six rabbits (one at 1 week, one at 2 weeks and four at 4 weeks), and plastic stents migrated in three rabbits (one at 2 weeks and two at 4 weeks; p > 0.05). Esophageal wall remodeling (thinner epithelial and smooth muscle layers) was similar in both stented groups ( p > 0.05), and the esophagus wall was found to be significantly thinner in the stented groups than in the control group ( p < 0.05). Esophageal injury and collagen deposition following stent insertion were similar and did not differ from the control group ( p > 0.05). Conclusions: Esophageal silicone-covered magnesium stents provided reliable support for at least 2 weeks, with acceptable migration rates and without causing severe injury or tissue reaction compared with plastic stents.